The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1590/1980-5918.030.004.ao08
|View full text |Cite
|
Sign up to set email alerts
|

Sexuality and reproduction in women with spinal cord injury

Abstract: Introduction: Spinal cord injury (SCI) is debilitating and results in different social representations for the women affected in terms of their sexuality and reproduction. Objective: Describe the experience of women with SCI regarding sexuality and reproduction under these conditions. Methods: Participants were 11 women with SCI who were submitted to a semi-structured interview. The content of the interviews was inputted into ALCESTE software, a computerized technique used for text analysis. Results: The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 19 publications
0
3
0
1
Order By: Relevance
“…In one study, in which support of partner is necessary for happiness, fulfillment, and connectedness with other; This research also claimed that desire discrepancy was defined as the difference in desire between sexual partners, low discrepancy was positively related to both relationship and sexual satisfaction [15]. In another research discovered that women with SCI fear abandonment by their husband or the possibility of never having another relationship; however, these fears soon fade by their husband's acceptance of disability [10].…”
Section: Support Of Husbandmentioning
confidence: 96%
See 2 more Smart Citations
“…In one study, in which support of partner is necessary for happiness, fulfillment, and connectedness with other; This research also claimed that desire discrepancy was defined as the difference in desire between sexual partners, low discrepancy was positively related to both relationship and sexual satisfaction [15]. In another research discovered that women with SCI fear abandonment by their husband or the possibility of never having another relationship; however, these fears soon fade by their husband's acceptance of disability [10].…”
Section: Support Of Husbandmentioning
confidence: 96%
“…This study discovered the present happiness of sexual life mean score below half of the normal range. Another research showed that subjects labelled their sex lives as worse after SCI, largely due to difficulties in their relationship with their partner, medical problems and the lack of privacy [10]. In contrast another study revealed that sexual function and SCI shows that sexual pleasure are possible for women having spinal cord injury [9].…”
Section: Happiness Of Sexual Lifementioning
confidence: 99%
See 1 more Smart Citation
“…Ainda são escassas as pesquisas sobre a sexualidade de mulheres acometidas por LM, porém, em decorrência do impacto da LM na vida das mulheres, o conhecimento sobre aspectos específicos da sexualidade feminina após a lesão poderá contribuir para intervenções que visem à melhoria do bem-estar biopsicossocial deste grupo. Tendo em vista que existem poucos dados no Brasil (Sodré;Faro, 2008;Matão, 2017), este estudo tem por objetivo avaliar o impacto da lesão medular na sexualidade de mulheres.…”
Section: Introductionunclassified